PEMBENTUKAN MODAL PEDAGANG PENJUAL MAKANAN DI KAWASAN PESISIR PANTAI MALALAYANG II KECAMATAN MALALAYANG KOTA MANADO - Fransisco Magofa; Victoria E.N. Manoppo; Grace O. Tambani; Djuwita R.R. Aling; Christian R. Dien; Olvie V. Kotambunan (Universitas Sam Ratulangi, 2023)
Abstract The aim of this research is to know and analyze the capital formation of traders who sell food on the coast of Malalayang II Beach, Malalayang District, Manado City. This research was conducted in the Malalayang II Village, Malalayang District, Manado City. The research time is approximately 5 months, from August to December 2022.The method used in this research is survey method. The data collected in this study consisted of primary data and secondary data. The data analysis technique used in this study is descriptive analysis. The data obtained in the research is made in a simpler form so that it is easy to understand. In order to answer the research objectives, the data needed includes: a description of the food seller's business, as well as their daily activities, while for the needs of age, education, condition of the house where they live, length of time doing business, side jobs are needed as food seller profile data and economic data in the form of capital, operating income and operating expenses.Based on the results of the study, it can be concluded that the formation of capital for traders who sell food on the coast of Malalayang II Beach, Malalayang District, Manado City comes from their own savings, the help of parents and close relatives. There is capital for investment, capital for operations and loan capital.Â Keywords: culinary, capital formation, coast, Malalayang Beach Â Abstrak Tujuan penelitian mengetahui serta menganalisis pembentukan modal pedagang yang menjual makanan di pesisir Pantai Malalayang II Kecamatan Malalayang Kota Manado. Penelitian ini dilaksanakan di Kelurahan Malalayang II Kecamatan Malalayang Kota Manado. Waktu penelitian kurang lebih 5 bulan, yaitu dari bulan Agustus sampai Desember 2022. Metode yang digunakan dalam penelitian ini ialah metode survei. Data yang dikumpulkan pada penelitian ini terdiri dari data primer dan data sekunder. Teknik analisis data yang digunakan pada penelitian ini adalah analisis deskriptif. Data yang diperoleh dalam penelitian dibuat dalam bentuk yang lebih sederhana agar mudah dipahami. Guna menjawab tujuan penelitian, data yang diperlukan antara lain: deskripsi usaha penjual makanan, serta aktivitas mereka sehari-hari, sedangkan untuk kebutuhan umur, pendidikan, keadaan rumah tempat tinggal, lamanya menjalani usaha, pekerjaan sampingan diperlukan sebagai data profil penjual makanan dan data ekonomi berupa permodalan, pendapatan usaha serta pengeluaran operasional. Berdasarkan hasil penelitian dapat disimpulkan bahwa pembentukan modal pedagang yang menjual makanan di pesisir Pantai Malalayang II Kecamatan Malalayang Kota Manado berasal dari tabungan sendiri, bantuan orang tua dan saudara dekat. Ada modal untuk investasi, modal untuk operasional dan modal pinjaman. Â Kata kunci: kuliner, pembentukan modal, pesisir, Pantai Malalayang